PERBANDINGAN DESAIN RUKO DI INDONESIA DITINJAU DARI ASPEK SOSIAL DAN PEMBENTUKAN KOMUNITAS - Sugiharto, Nathalia Yunita (ARTEKS Jurnal Teknik Arsitektur, 2017)
Title: Indonesian Shophouse Design Development based on the Establishment of Community and Social Aspect The existence of shophouse in Indonesia has been started in the 17th century at the Colonial Era brought by Chinese traders.Shophouse is considered as a solution of the increasing density of population in Indonesia and land limitation. Shophouse typology adapt along with time and its surroundings. Along with its development, nowadays shophouse’s design had its own problem. Basically shophouse is supposed to accomodate two functions which is residential and stores but its residential function become less dominant than its commercial function. One of the causes is the shophouse design can’t meet the resident’s social needs satisfaction. Method that used in this research is comparative by comparing shophouse design in Colonial era with shophouse design that commonly found in Indonesia. Based on the study, it showed that the shophouse design in Colonial era was able to accommodate social functions among the inhabitants while the shophouse design that is commonly found in Indonesia focused in terms of economy (how quickly sold) and ignore the residential needs in their design. The study is expected to provide benefits in shophouse design in future and can contribute the knowledge in the realm of architecture. Keywords: shophouse, social,  facilities, community, development